Takhrij Hadis tentang Keutamaan Salat Berjamaah dalam Kitab Sahih Bukhari - Asri Asri; Nidaul Hana; Fajar Arifin; A. Faizal Khasani (Kampus Akademik Publiser, 2026)
Abstract. Prayer (salat) is the second pillar of Islam, and its congregational form (salat berjama’ah) holds a special place in Islamic teaching due to its spiritual and social dimensions. This study aims to examine the hadith on the virtue of congregational prayer contained in Sahih Bukhari, particularly hadith number 662, through the methodology of takhrij hadith. The research employs a qualitative descriptive approach with library research method. Primary data were drawn from the hadith text in Sahih Bukhari, while secondary data were gathered from classical and contemporary works on hadith sciences, Islamic jurisprudence, and related journal articles. The takhrij process involved tracing the hadith back to its original source, identifying the chain of transmission (sanad), and evaluating the credibility of each narrator based on the principles of jarh wa ta’dil. The findings indicate that Hadith No. 662 in Sahih Bukhari, narrated from Anas ibn Malik through a continuous and sound chain of transmission, instructs the straightening and closing of prayer rows (saf). The hadith is classified as sahih (authentic) based on the high reliability of all narrators in its chain. The content of the hadith demonstrates that proper row alignment in congregational prayer is a prophetic directive with significant implications for discipline, unity, and social solidarity among Muslims. This study concludes that the hadith provides a solid religious foundation for the practice of congregational prayer and conveys values relevant to contemporary Muslim life. Keywords: Congregational Prayer; Hadith Authentication; Sanad; Sahih Bukhari; Takhrij Hadith